Peningkatan Pemasaran Produk Jamu Tradisional Loloh Cemcem melalui Pemasaran Digital di Desa Kintamani: Marketing of Loloh Cemcem Traditional Herbal Products through Digital Marketing in Kintamani Village - I Putu David Adi Saputra; Kadek Feni Aryati (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The increasing interest in traditional herbal medicine like Loloh Cemcem in Kintamani Village faces challenges in digital marketing and market access. Producers lack the skills and resources to promote their products beyond the local area, limiting income and business growth. This community service program aims to improve the marketing of Loloh Cemcem through digital marketing training, covering content creation, social media management, online advertising, and SEO. The program includes a three-day workshop and six months of mentoring, supported by internet access and necessary tools. Target outcomes include a 25% sales increase, 50% growth in social media followers, and improved digital marketing skills. This initiative focuses on empowering local micro-enterprises and aims to sustainably boost the village economy through better marketing of traditional herbal products.